Substituent Effect Transmission Power of Alkyl, Alkenyl, Alkynyl, Phenyl, Thiophenyl, and Polyacene Spacers. Issue 13 (13th June 2019) - Divya, Velayudhan V.; Sayyed, Fareed Bhasha; Suresh, Cherumuttathu H.
Abstract: The transmission of substituent effect through a variety of spacers, that is to say, alkyl, alkenyl, alkynyl, phenyl, thiophenyl, and polyacene has been studied by modeling Y‐G‐X type molecular systems (Y: reaction center; G: spacer moiety; X: substituent) using B3LYP/6‐31G(d, p) density functional theory calculations. The reaction center is always kept as a C=C double bond and the molecular electrostatic potential (MESP) minimum ( V min ) observed for this bond showed subtle variation with respect to the changes in the spacer unit and the nature of substituent. Strong linear correlations are observed between Hammett substituent constants (σI and σp ) and Vmin, which recommend the aptness of V min as an electronic descriptor to quantify the substituent effect. Since V min offers an alternative measure of substituent effect, the correlation between V min and σ p has been used for assessing the transmission of substituent effect through a variety of spacer moieties. The highest transmission coefficient (γ) is always observed for smaller spacer length. Among all the spacers, alkenyl showed the highest and alkyl showed the lowest transmission power. The study recommends the use of short chains of C=C double, C≡C triple or a combination of both as spacers for the effective transmission of substituent effect to the reaction center. Abstract : Through space(rs) : The molecular electrostatic potential (MESP) minimum ( V min ) at the terminal C=C double bond is used to quantify the transmission power of substituent effect through various spacers.